Determinan Adopsi Sistem Informasi Akuntansi Digital Pada UMKM: A Systematic Literature Review And Research Agenda - Ria Fransisca Ifa Evendy Ria Fransisca Ifa Evendy; Bella Novianti Kurnia (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2026)
Despite rapid digitalization, the adoption of Digital Accounting Information Systems (AIS) among Small and Medium Enterprises (SMEs) remains significantly low. Existing literature on AIS adoption is fragmented, lacking comprehensive synthesis of adoption determinants. This Systematic Literature Review employs the PRISMA 2020 protocol to synthesize findings from 110 peer-reviewed articles published between 2015–2026 from Scopus and Science Direct. The study identifies six major theoretical contributions: (1) hybrid adoption models integrating Technology-Organization-Environment (TOE), Unified Theory of Acceptance and Use of Technology (UTAUT), and Resource-Based View (RBV); (2) paradigm shift from pre-adoption intention to post-adoption value creation; (3) TOEO framework emphasizing ownership as a critical determinant; (4) integration of Innovation Resistance Theory addressing psychological barriers; (5) extension of Information Systems Success Model (ISSM) and Expectation-Confirmation Model (ECM) to SME contexts; and (6) AIS as a dynamic capability and strategic resource. The study identifies 28 adoption determinants (24 enablers, 4 barriers). Key enablers include perceived usefulness (78 studies), perceived ease of use (65 studies), and top management support (58 studies), while implementation cost (52 studies) and technical skill gaps (47 studies) are primary barriers. Recommendations target government (subsidy programs, digital literacy training, regulatory frameworks), vendors (user-friendly interfaces, flexible pricing, continuous support), and SME owners (strong leadership, resource allocation, strategic AIS integration). This research advances technology adoption theory and provides practical guidance for sustainable digital transformation in SMEs.